Mustard seeds derived fluorescent carbon quantum dots and their peroxidase-like activity for colorimetric detection of H 2 O 2 and ascorbic acid in a real sample - Chandra S.; Singh V.K.; Yadav P.K.; Bano D.; Kumar V.; Pandey V.K.; Talat M.; Hasan S.H. (My University, 2025)
Herein, we were synthesized fluorescent carbon quantum dots via facile one-step hydrothermal treatment of mustard seeds (M-CQDs). It showed excellent optical property with fluorescent quantum yield 4.6%. The as-prepared M-CQDs exhibited peroxidase-like mimetic activity and catalyzed the oxidation of chromogenic substrate 3,3‘,5,5‘-tetramethylbenzidine (TMB) in the presence of H 2 O 2 to produce a blue color reaction mixture with the prominent peak at 652 nm. Furthermore, the peroxidase-like catalytic performance of M-CQDs followed the steady-state kinetics behavior and exhibited similar catalytic activity as that of natural enzyme Horseradish peroxidase (HRP). In addition to this, the double reciprocal plot showed a parallel line which suggested the occurrence of Ping-Pong type of mechanism. The H 2 O 2 dependent oxidation of TMB was helpful for the colorimetric detection of H 2 O 2 in the linear range of 0.02–0.20 mM with the limit of detection (LOD) of 0.015 mM. Interestingly, the oxidized TMB (ox-TMB) was further reduced to native TMB by the reducing agent ascorbic acid. Hence M-CQDs showed its potential towards the selective and sensitive detection of ascorbic acid in the linear range of 10–70 μM having a correlation coefficient of 0.998 with LOD of 3.26 μM. The practical feasibility of the proposed detection method of AA was also investigated in common fresh fruits. © 2018 Elsevier B.V.